The movements of Shoveler ringed in Britain - Ogilvie, M A (Wildfowl, 1962)
Shoveler breeding and bred in Great Britain tend to move south in autumn and winter, some travelling as far as south-west Spain, the Camargue and central Italy. Few seem to be wholly sedentary. No clear case of abmigration has been found. Ringing in autumn and winter in southern England and Wales reveals differences in the movements of Shoveler caught from August to October and those caught from November to February. While recoveries in winter of birds from both groups show a mainly southerly scatter like that of the breeding birds, the winter-ringed birds have provided a relatively large proportion of recoveries around the Baltic and east into the U.S.S.R. This suggests that winter visitors and passage-migrants from the north-east tend to arrive in England quite late, Shoveler are probably most numerous in England in March, but hardly any have been ringed at that time so that the movements of these late-winter and spring visitors are not yet understood.